Model Planning of Maintenance Dredging (Study Case: East Java Pultipurpose Terminal at Lamongan Shorebase) - Tasya Putri Rhamadani; Muhammad Zikra; Kriyo Sambodho (International Journal of Offshore and Coastal Engineering, 2025)
As one of the important entities in the sea transportation process chain, the port has a vital role as a connection point between regions. East Java Multipurpose Terminal (EJMT) is one of the port terminals which will be used as a connection point for the distribution of goods, especially around East Java Province. The purpose of this paper is to obtain effective and efficient model scenario for maintenance dredging plan at EJMT. The method used in this research is optimization method with a non-linear algorithm approach to determine the minimum cost. The results of this study indicate that the dredging scenario using sediment traps is the most optimum with the total volume of material dredged is 107,671.61 m3. The total duration of the dredging work is around 7 days with total cost around 7.1 billion rupiah or equivalent to 65-70 thousand rupiah per cubic meter